AKIBAT HUKUM PENDAFTARAN OBJEK JAMINAN FIDUSIA DI DALAM PERJANJIAN KREDIT - Indra Eka Putra, I Dewa Gede; Subha Karma Resen, Made Gde (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 06, Juli 2013)
This writing shall be entitled as “Legal Implication of Warrant Object Registration as Fiduciary in Credit Agreement”. This writing applied normative legal research. Fiduciary had been regulated pursuant to Law No. 42 of 1999, stipulating that a debtor is obliged to register its warrant object in Fiduciary Registration Office whereas, such occurrences had been observed as extremely rare, mostly upon the reason of mere efficiency and competitiveness among institutions. Upon such grounds, this writing shall illustrate the legal implication once the debtor is not registering its warrant to the Fiduciary Registration Office.
Keywords: Credit Agreement, Fiduciary Warrant